-0.28p-0.06(2-6p)=0.06(p-2)-0.1

Simple and best practice solution for -0.28p-0.06(2-6p)=0.06(p-2)-0.1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -0.28p-0.06(2-6p)=0.06(p-2)-0.1 equation:


Simplifying
-0.28p + -0.06(2 + -6p) = 0.06(p + -2) + -0.1
-0.28p + (2 * -0.06 + -6p * -0.06) = 0.06(p + -2) + -0.1
-0.28p + (-0.12 + 0.36p) = 0.06(p + -2) + -0.1

Reorder the terms:
-0.12 + -0.28p + 0.36p = 0.06(p + -2) + -0.1

Combine like terms: -0.28p + 0.36p = 0.08p
-0.12 + 0.08p = 0.06(p + -2) + -0.1

Reorder the terms:
-0.12 + 0.08p = 0.06(-2 + p) + -0.1
-0.12 + 0.08p = (-2 * 0.06 + p * 0.06) + -0.1
-0.12 + 0.08p = (-0.12 + 0.06p) + -0.1

Reorder the terms:
-0.12 + 0.08p = -0.12 + -0.1 + 0.06p

Combine like terms: -0.12 + -0.1 = -0.22
-0.12 + 0.08p = -0.22 + 0.06p

Solving
-0.12 + 0.08p = -0.22 + 0.06p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-0.06p' to each side of the equation.
-0.12 + 0.08p + -0.06p = -0.22 + 0.06p + -0.06p

Combine like terms: 0.08p + -0.06p = 0.02p
-0.12 + 0.02p = -0.22 + 0.06p + -0.06p

Combine like terms: 0.06p + -0.06p = 0.00
-0.12 + 0.02p = -0.22 + 0.00
-0.12 + 0.02p = -0.22

Add '0.12' to each side of the equation.
-0.12 + 0.12 + 0.02p = -0.22 + 0.12

Combine like terms: -0.12 + 0.12 = 0.00
0.00 + 0.02p = -0.22 + 0.12
0.02p = -0.22 + 0.12

Combine like terms: -0.22 + 0.12 = -0.1
0.02p = -0.1

Divide each side by '0.02'.
p = -5

Simplifying
p = -5

See similar equations:

| f(x)=5x^4+3x+7 | | 12,000/52=x/1 | | 104+8x=107+7x | | 79+9x=94+4x | | 2(6+-7x+2x^2)=0 | | 10-.33333y=4+6x | | 9q^2+9q-10=0 | | 49=7j | | 4+5w-4w=4-2 | | z-7=36 | | 2-(1/4) | | (5x)+(x+20)+(2x)=180 | | 4+9(x)=184 | | (9*sqr-1)8(-6*sqr-4)= | | 20=x-4 | | w-50=16 | | -14=(6/7)x-4-7x | | (9*((-1)^1/2)*((-6)((-4)^1/2))= | | 6x-7=1+4x | | 47=p+14 | | 0.04(y-8)+0.02y=0.16y-0.9 | | -14=(6/7x)-4-7x | | 10x=3+12 | | (3w^2-7w+2)+(-4w^2+5w+1)= | | 5x-(7)=7x-(17) | | -3x-6=18forx | | 10x+4x+3+7=9x+3+4x | | 18=3d | | 8=(10)w(2) | | ln(y)=2ln(x)+ln(10) | | 23x+21x=72 | | h-23=27 |

Equations solver categories